Driven transport on parallel lanes with particle exclusion and obstruction - Melbinger, Anna; Reichenbach, Tobias; Franosch, Thomas; Frey, Erwin (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2011)
We investigate a driven two-channel system where particles on different lanes mutually obstruct each other's motion, extending an earlier model by Popkov and Peschel. This obstruction may occur in biological contexts due to steric hinderance where motor proteins carry cargos by "walking" on microtubules. Similarly, the model serves as a description for classical spin transport where charged particles with internal states move unidirectionally on a lattice. Three regimes of qualitatively different behavior are identified, depending on the strength of coupling between the lanes. For small and large coupling strengths the model can be mapped to a one-channel problem, whereas a rich phase behavior emerges for intermediate ones. We derive an approximate but quantitatively accurate theoretical description in terms of a one-site cluster approximation, and obtain insight into the phase behavior through the current-density relations combined with an extremal-current principle. Our results are confirmed by stochastic simulations. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2021-02-25